APLIKASI TERAPI KOGNITIF PERILAKU UNTUK MENANGANI KONFLIK PERKAWINAN PADA PASANGAN YANG BEKERJA (DUAL-EARNER) - BAIQ ROHASLIA RHADIANA; CARLA R. MACHIRA; IRWAN SUPRIYANTO (JURNAL ILMIAH KOHESI, 2022)
Behavioral cognitive therapy in this case can be a therapeutic option in dealing with marital conflicts in dual-earner couples, given that in principle it can be used for different backgrounds of the patient. This therapy is also widely researched to address depression, anxiety, anger management, and marital problems. This study aims to solve problems that are closely related to marriage problems for working couples The research method used in this study is descriptive qualitative. The results of the study concluded Behavioral cognitive therapy can be used to deal with marital conflicts in equally working couples (dual-earners). The application of behavioral cognitive therapy to overcome marital conflicts for dual-earners is implemented through a comprehensive assessment and implementation techniques. Termination can be done if communication between spouses is more.